A next-generation strategy for HIV-1 vaccination: computational design of a multi-epitope subunit vaccine targeting global circulating variants - Khan, Sajid; Attique, Zarlish; Hamza, Muhammad; Li, Lingyu; Imran, Muhammad; Yu, Li; Zhang, Suping (Frontiers in Virology, 2026)
Despite decades of research, no effective cure or preventive vaccine exists for human immunodeficiency virus type 1 (HIV-1). To address this gap, this study aimed to design a universal multi-epitope subunit vaccine (MESV) targeting conserved and immunogenic epitopes across diverse HIV-1 variants. Publicly available HIV-1 proteome data were analyzed using an immunoinformatics pipeline that integrates curated immunological databases and epitope-prediction servers, resulting in the identification of 44 conserved epitopes from the core proteome, including twelve newly identified relative to existing databases. The MESV was constructed using 14 linear B-cell epitopes and 30 T-cell epitopes restricted by globally conserved human leukocyte antigen (HLA) alleles, achieving 98.63% MHC-I and 99.67% MHC-II global population coverage. Molecular docking analysis revealed high binding scores and favorable energy values for MESV interactions with toll-like receptor 1 (TLR1) and toll-like receptor 2 (TLR2), suggesting stable antigen recognition. After codon optimization, the MESV (889 aa) was expressed and purified using affinity chromatography, yielding an ~95.1 kDa protein confirmed by immunoblot analysis. In silico immunological simulations demonstrated robust humoral and cellular immune responses following three doses, including elevated IgG antibody levels and increased numbers of memory B cells, cytotoxic CD8+ T cells, and natural killer cells. Overall, this study highlights the potential of a computationally designed MESV to overcome HIV-1 diversity and induce broad-spectrum immunity. These findings warrant further in vitro and in vivo validation to confirm immunogenicity and protective efficacy, paving the way toward the development of a universal HIV-1 vaccine.